An Algorithm of Auto-Update Threshold for Singularity Analysis of Pipeline Pressure - Ma, Dazhong; Tan, Liang; Feng, Jian; Liu, Jinhai (Mathematical problems in engineering, 2013)
A precise auto-update threshold algorithm (AUTA) which imitates the short-term memory of human brain is proposed to search singularities in pipeline pressure signal. According to the characteristics of the pressure signal, the pressure can be divided into two states known as nonsteady state and steady state. The AUTA can distinguish these two states and then choose corresponding method to calculate the dynamic thresholds of pressure variation in real time. Then, the parameters of AUTA are analyzed to determine their values or ranges. Finally, in the simulations to the actual pressure signal from oil pipelines, we verified the effectiveness of AUTA in estimating the dynamic threshold value of pressure.